Fair division in unanimity bargaining with subjective claims - Anita Gantner; Kristian Horn; Rudolf Kerschbamer (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2013)
In an experiment on a subjective claims problem we compare three unanimity bargaining procedures - the Demand, the Offer and the Exit variant - in terms of fairness and efficiency. To assess the fairness of the allocations obtained by these procedures, we evaluate them from a partial point of view using stakeholders' subjective evaluations of claims as elicited in a hypothetical fairness question, and we evaluate them from an impartial point of view using spectators' responses in a vignette. We find that after correcting for the self-serving bias in the partial view, both views point towards the same allocation. The Offer variant, which requires stakeholders to supply complete division proposals, yields outcomes that come closest to this fair allocation.
Keywords: D63; C91; D61; 330; Fair Division; Subjective Claims; Bargaining; Experiment